Generalized Cash Flow Taxation - Alan Auerbach; David Bradford (Center for Economic Studies and ifo Institute (CESifo), 2001)
We show the unique form that must be taken by a tax system based entirely on realization accounting to implement a uniform capital income tax, or, equivalently, a uniform wealth tax. This system combines elements of an accrual based capital income tax and a traditional cash flow tax, having many of the attributes of the latter while still imposing a tax burden on marginal capital income. Like the traditional cash flow tax, this system may be integrated with a tax on labor income. We also show how such a tax can be supplemented with an optional accounting for a segregated subset of actively traded securities, subjected separately to mark-to-market taxation at the uniform capital income tax rate, to permit a fully graduated tax system applicable to labor income.
Keywords: 330